2010
DOI: 10.1253/circj.cj-10-0079
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Bezafibrate and Pravastatin in Patients With Coronary Artery Disease and High Levels of Remnant Lipoprotein

Abstract: Background: Remnant lipoproteinemia is a strong risk factor for cardiovascular (CV) diseases. This study examined which of 2 common lipid-lowering drugs (fibrates and statins) is more effective in patients with remnant lipoproteinemia and if lowering remnant lipoprotein levels can reduce CV risk. Methods and Results:Remnant lipoprotein levels were measured by an immunoseparation method (remnantlike lipoprotein particles cholesterol: RLP-C) in 274 patients with coronary artery disease and high RLP-C levels (≥5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…It has also been shown that high levels of RLP cholesterol are an independent risk for cardiovascular events in patients with glucose intolerance [32]. Previous studies reported a significant association between reduced RLP cholesterol levels and a decrease in cardiovascular events [13,32]. The present study showed that bezafibrate treatment effectively reduced RLP cholesterol levels, while treatment with either rosuvastatin alone or bezafibrate plus rosuvastatin also resulted in a reduction in RLP cholesterol levels.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It has also been shown that high levels of RLP cholesterol are an independent risk for cardiovascular events in patients with glucose intolerance [32]. Previous studies reported a significant association between reduced RLP cholesterol levels and a decrease in cardiovascular events [13,32]. The present study showed that bezafibrate treatment effectively reduced RLP cholesterol levels, while treatment with either rosuvastatin alone or bezafibrate plus rosuvastatin also resulted in a reduction in RLP cholesterol levels.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have also reported that HDL cholesterol levels increase and fasting blood glucose concentrations decrease after administration of lipid-lowering agents, such as statins and fibrates [11,13]. As the present study included only a small number of patients and was of relatively short duration, further studies are required to clarify the effects of either statin plus fibrate, statin alone, or fibrate alone on HDL cholesterol and fasting blood glucose levels.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Only recently intermediate-size (274 patients) RCT have demonstrated that bezafibrate was significantly better than pravastatin (a relatively weak statin) in reduction of cardiovascular events [65]. Anyway, even intensive statin therapy does not eliminate the cardiovascular risk associated with low HDL or/and high triglycerides (atherogenic dyslipidemia)!…”
Section: What Is the Place Of Fibrates In The Statins World?mentioning
confidence: 99%
“…A comparison of statins and bezafibrate showed a mild improvement in remnant-like lipoprotein cholesterol (RLP-C) with statins versus bezafibrate 27) . In another study of patients with coronary artery disease complicated by high remnant lipoproteinemia, bezafibrate, but not pravastatin, significantly decreased the RLP-C levels and, during the one-year follow-up period, significantly decreased the incidence of cardiovascular events 28) . Bezafibrate is thus a therapeutic option in cases of dyslipidemia associated with diabetes mellitus, as statins normalize only the LDL-C level, leaving remnant lipoproteins and small dense LDL as residual risk factors.…”
Section: Discussionmentioning
confidence: 90%